2022
DOI: 10.21203/rs.3.rs-1739437/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Journal of Insect Conservation Survival of eggs to third instar of late-summer and fall-breeding monarch butterflies (Danaus plexippus) and queen butterflies (Danaus gilippus) in north Texas

Abstract: Introduction: Eastern migratory monarch butterflies (Danaus plexippus) have declined over 80% in recent years, but little is known about fall reproduction in the southern U.S. where monarchs may compete with queen butterflies (Danaus gilippus). Aims/Methods: We provide data on the survival to third instar, associated arthropods, and phenology of fall breeding monarchs and queens in Texas. Results: Monarch and queen survival was high, but varied among years. Oleander aphids (Aphis nerii), jumping spiders (Salti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Calvert (2004) later reported that monarch larval survival is higher within small exclosures (~20 m 2 ) treated for fire ants than outside. In contrast, other researchers in Texas reported that a higher percentage of monarchs survived to third instars closer to red imported fire ant mounds than farther away from fire ant mounds (Hudman 2018) and that fire ants had no significant effect on fifth instar survival (Scott 2019). Monarch survival from egg to fifth instar is very low (7–10%; Nail et al 2015) even in areas without fire ants, so it is not clear if fire ants decreased monarch survival, or if fire ants removed or replaced other predators (Calvert 2004, Hudman 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Calvert (2004) later reported that monarch larval survival is higher within small exclosures (~20 m 2 ) treated for fire ants than outside. In contrast, other researchers in Texas reported that a higher percentage of monarchs survived to third instars closer to red imported fire ant mounds than farther away from fire ant mounds (Hudman 2018) and that fire ants had no significant effect on fifth instar survival (Scott 2019). Monarch survival from egg to fifth instar is very low (7–10%; Nail et al 2015) even in areas without fire ants, so it is not clear if fire ants decreased monarch survival, or if fire ants removed or replaced other predators (Calvert 2004, Hudman 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Conservation practitioners would also benefit from an improved understanding of how monarchs and pollinators interact with habitats of varying quality. We recognize that the sites surveyed and flowering species documented may not offer equal value to monarchs (Nail et al, 2015;Grant et al, 2020;Antonsen et al, 2021;Bruce et al, 2022;Scott et al, 2023). The IMMP's surveys of adult and immature monarchs offer opportunities to explore such relationships.…”
Section: Future Directionsmentioning
confidence: 99%